Major challenges to agricultural development mark CTA's first decade - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Ten years have passed since CTA's first staff members were appointed. In the history of what we nowadays call 'development', and of the young nations of the ACP Group, ten years is a relatively long period. What changes and events have characterized...